2015
DOI: 10.1371/journal.pgen.1005120
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology of Tissue-Specific Response to Anaplasma phagocytophilum Reveals Differentiated Apoptosis in the Tick Vector Ixodes scapularis

Abstract: Anaplasma phagocytophilum is an emerging pathogen that causes human granulocytic anaplasmosis. Infection with this zoonotic pathogen affects cell function in both vertebrate host and the tick vector, Ixodes scapularis. Global tissue-specific response and apoptosis signaling pathways were characterized in I. scapularis nymphs and adult female midguts and salivary glands infected with A. phagocytophilum using a systems biology approach combining transcriptomics and proteomics. Apoptosis was selected for pathway-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
225
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(238 citation statements)
references
References 57 publications
(84 reference statements)
13
225
0
Order By: Relevance
“…However, it has been demonstrated that the tick response to infection is a complex and dynamic process with tissuespecific differences (8). In an attempt to address this issue, a preliminary and complementary analysis of tissue-specific differences in response to infection of I. scapularis nymphs and adult female guts and salivary glands was included in the study.…”
Section: Dynamics and Tissue Specificity Of The Effect Of A Phagocytmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been demonstrated that the tick response to infection is a complex and dynamic process with tissuespecific differences (8). In an attempt to address this issue, a preliminary and complementary analysis of tissue-specific differences in response to infection of I. scapularis nymphs and adult female guts and salivary glands was included in the study.…”
Section: Dynamics and Tissue Specificity Of The Effect Of A Phagocytmentioning
confidence: 99%
“…Other hemolymph effector proteins associated with tick hemocytes such as defensins, Complement-like molecules and antimicrobial peptides were also identified and, although not differentially represented between infected and uninfected cells (Supplemental Table V), could serve as biomarkers for hemocyte-like function of ISE6 tick cells (51). Recent results showed how the I. scapularis nymphs and adult female guts and salivary glands respond to A. phagocytophilum infection at both RNA and protein levels (8). Using those results and the results reported in the present study, the expression/representation of selected genes/proteins involved in the protein processing in ER and glucose metabolic pathways were compared between in vitro and in vivo studies (Fig.…”
Section: Dynamics and Tissue Specificity Of The Effect Of A Phagocytmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ayllón et al (2015) showed that A. phagocytophilum (NY18) inhibits the intrinsic apoptosis pathway through porin downregulation to prevent Cytochrome c release in I. scapularis salivary glands. To characterize this mechanism in vitro, gene knockdown by RNAi was used for functional characterization of the porin gene during…”
Section: Ire/ctvm20 Cellsmentioning
confidence: 99%